Association of Time of Delivery With Composite Adverse Outcomes in Low-Risk Pregnancies. Issue 3 (March 2020) - Wagner, Stephen M.; Chen, Han-Yang; Gupta, Megha; Chauhan, Suneet P.
Abstract : OBJECTIVE: To compare the composite neonatal and maternal adverse outcomes among low-risk pregnant women who labor and subsequently deliver at different time shifts. METHODS: This was a population-based retrospective cohort study using the U.S. vital statistics data set on Period Linked Birth-Infant Death Data from 2012 to 2016. The study population was restricted to live births from low-risk women with nonanomalous singletons who labored and delivered at 37 0/7 to 41 6/7 weeks of gestation. Time of delivery was categorized as the first shift (7:00–15:00), the second shift (15:00–23:00), and the third shift (23:00–7:00). The primary outcome was composite neonatal adverse outcome, and the secondary outcome was composite maternal adverse outcome. Multivariable Poisson regression models were used to estimate the association between the time of delivery and adverse outcomes (using adjusted relative risk [aRR] and 95% CI). RESULTS: Of 19.9 million live births during the study period, 58.8% (more than 11.6 million) met the inclusion criteria. The overall composite neonatal adverse outcome was 6.6 per 1, 000 live births. The multivariable adjusted analysis demonstrated that, compared with neonates delivered at the first shift, the risk of composite neonatal adverse outcome was higher at the second shift (relative risk [RR] 1.15, aRR 1.07, 95% CI 1.05–1.09), and the third shift (RR 1.28, aRR 1.24, 95% CI 1.22–1.27). The overall composite maternal adverse outcome was 2.45 per 1, 000 live births. After adjustment, there was no significant difference in the risk of composite maternal adverse outcome based on the time of delivery. CONCLUSION: Among low-risk singleton pregnancies, compared with delivery at 7:00–15:00, the composite neonatal adverse outcome is marginally but significantly higher if the delivery occurs at the second (15:00–23:00) and the third (23:00–7:00) shifts. The composite maternal adverse outcome is similar among the three different time shifts. Abstract : Among low-risk pregnancies, composite neonatal adverse outcome reaches a nadir with delivery between 7:00 and 15:00; composite maternal adverse outcome remains consistent by delivery time.